Media sosial sebagai alat promosi terhadap minat peserta didik - Novriyansah, M. Anasrul Dwi; Afgani, Muhammad Win; Afriantoni (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
In the development of information and communication technology, various visual media have been used as educational media, including social media. The point of using social media networks for teaching and learning purposes is that not many people practice it. Social media has now become a lifestyle, especially for the millennial generation, who use social media not only to build friendships between people, but also in the field of marketing and institutional or corporate organizations. Everyone now uses social media to convey information to the public. Even in a business, social media is a product promotion tool, but now it is not only business institutions but also educational institutions or schools. Therefore, this research discusses the influence of social media as a promotional tool on student interest. Keywords: Learner Interest; Promotion Tools; Social Media Abstrak Dalam perkembangan teknologi Informatika dan komunikasi berbagai media visual dijadikan sebagai media pendidikan termasuk media sosial titik pemanfaatan jejaring media sosial untuk kepentingan belajar mengajar memang belum banyak yang mempraktikkannya. Media sosial saat ini sudah menjadi gaya hidup khususnya para generasi milenial penggunaan media sosial tidak hanya untuk menjalin pertemanan antar manusia, tapi juga dalam bidang marketing dan organisasi lembaga atau perusahaan. Semuanya kini menggunakan media sosial untuk menyampaikan informasi kepada masyarakat. Bahkan dalam sebuah bisnis media sosial menjadi alat promosi produk namun sekarang tidak hanya lembaga bisnis saja tetapi juga lembaga pendidikan atau sekolah. Oleh karena itu penelitian ini membahas pengaruh media sosial sebagai alat promosi terhadap minat peserta didik.